ANALISIS PENGARUH PENGELUARAN KONSUMSI PEMERINTAH DAN PENGELUARAN KONSUMSI RUMAH TANGGA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 1988-2017 - Ari Tri Afiftah; Whinarko Juliprijanto; Rian Destiningsih (Universitas Tidar, 2019)
Economic growth is one measure of the success of a country's development. In Indonesia for the last 30 years, from 1988 to 2017, economic growth has fluctuated but tends to be stable. The rapid development in Indonesia has an impact on increasing living standards and people's welfare. This research is quantitative descriptive. The data in this study used secondary data published by the Indonesian Central Bureau of Statistics (BPS) Indonesia in 1988 to 2017. Data analysis techniques used time series data analysis with multiple linear regression analysis techniques. The results of the study show that: (1) Variables of government consumption expenditure partially indicate a significant influence on economic growth in Indonesia in 1988-2017; (2) Variables of household consumption expenditure partially indicate a significant influence on economic growth in Indonesia in 1988-2017; (3) Variables of government consumption expenditure and household consumption expenditure together have a significant influence on economic growth in Indonesia in 1988-2017. Keyword : government consumption expenditure, household consumption expenditure, and economic development